Effects of increasing concentrations of an Escherichia coli phytase on the apparent ileal digestibility of amino acids and the apparent total tract digestibility of energy and nutrients in corn-soybean meal diets fed to growing pigs. (24th April 2018) - She, Yue; Sparks, J Chris; Stein, Hans H
Abstract: An experiment was conducted to test the hypothesis that inclusion of increasing concentrations of an Escherichia coli phytase to a corn–soybean meal (SBM ) diet results in improved digestibility of DM, GE, CP, NDF, ADF, macrominerals, microminerals, and AA. Twenty-four growing barrows (initial BW: 37.0 ± 1.4 kg) were equipped with a T-cannula in the distal ileum and placed individually in metabolism crates, and allotted to a 2-period switch-back design with 6 diets and 4 replicate pigs per diet in each period. The positive control diet was a corn–SBM diet that contained limestone and dicalcium phosphate to meet the requirement for standardized total tract digestible (STTD ) P and Ca (0.31% STTD P and 0.70% Ca). A negative control diet that was similar to the positive control diet, with the exception that no dicalcium phosphate was used, was also formulated, and this diet contained 0.16% STTD P and 0.43% Ca. Four additional diets were formulated by adding 500, 1, 000, 2, 000, or 4, 000 units of microbial phytase (FTU ) to the negative control diet. Each period lasted 14 d. Fecal and urine samples were collected from the feed provided from days 6 to 11 of each period following 5 d of adaptation to the diets. Ileal digesta were collected for 8 h on days 13 and 14. Results indicated that addition of the E. coli phytase to the negative control diet tended to quadratically improve the apparent ileal digestibility of Phe ( P = 0.086) and Asp ( P = 0.054), and linearly increased ( P < 0.05) the apparent total tract digestibility (ATTD ) of ADF, K, and Fe. Microbial phytase also quadratically increased ( P < 0.05) the ATTD of NDF and Mg, and linearly and quadratically increased ( P < 0.05) the ATTD and retention of Ca and P. However, no effects of the phytase on ATTD of GE or the concentration of DE were observed. In conclusion, the increased absorption of several minerals including Ca, P, K, Mg, and Fe that was observed as increasing concentrations of an E. coli phytase was added to a corn–SBM meal diet indicates that the dietary provision of these minerals may be reduced if phytase is fed.